1973
DOI: 10.1159/000122193
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fornix Transection or Hippocampectomy on Rhythmic Pituitary-Adrenal Function in the Rat

Abstract: To determine whether the hippocampo-fornix system is essential for the circadian rhythm in non-stress pituitary-adrenal function, adult female rats were subjected to fornix transection or hippocampectomy. Non-stress plasma corticosterone levels, measured fluorometrically in blood samples obtained at different times during the 24 h light-dark cycle, were used to assess rhythmic pituitary-adrenal function. At 1–2 and 4–5 weeks after surgery, morning and afternoon non-stress plasma corticosterone levels were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

1974
1974
1985
1985

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…Hippo campus has been intermittently identified with the control of neuroendocrine functions, al though the results have been somewhat in consistent and conflicting. Electrical stimula tion of hippocampus in the rat is associated with increases in serum GH concentration [37], and hippocampal ablation slows down the rate of weight gain in young male animals [71] suggesting a facilitatory role of hippo campal formation in the control of GH secre tion and somatic growth in this species. Elec trical stimulation and ablation studies have, furthermore, implicated hippocampal forma tion in facilitation of thyroid hormone release in the dog [58], in inhibition of ovulation [39], in modulation of diurnal rhythms of glucocor ticoid secretion [45] in the rat, in maintenance of low basal glucocorticoid secretory rates in rats and cats [21,29,30], and in suppression of stress-induced glucocorticoid release in the rat [30], Presence of high density of gluco corticoid receptors in hippocampal tissue [38] prompted the idea that glucocorticoid uptake by hippocampal cells may serve as a negative feedback to its putative inhibitory function over glucocorticoid secretion, but hormone implantation in the hippocampus has yielded contradictory results [67], It would be of interest to determine whether the growth suppressing and GH-inhibitory functions of hippocampal formation (present study and Borer et al [11] and of the rostral medial septal area [9] are mediated by somato statin.…”
Section: Discussionmentioning
confidence: 99%
“…Hippo campus has been intermittently identified with the control of neuroendocrine functions, al though the results have been somewhat in consistent and conflicting. Electrical stimula tion of hippocampus in the rat is associated with increases in serum GH concentration [37], and hippocampal ablation slows down the rate of weight gain in young male animals [71] suggesting a facilitatory role of hippo campal formation in the control of GH secre tion and somatic growth in this species. Elec trical stimulation and ablation studies have, furthermore, implicated hippocampal forma tion in facilitation of thyroid hormone release in the dog [58], in inhibition of ovulation [39], in modulation of diurnal rhythms of glucocor ticoid secretion [45] in the rat, in maintenance of low basal glucocorticoid secretory rates in rats and cats [21,29,30], and in suppression of stress-induced glucocorticoid release in the rat [30], Presence of high density of gluco corticoid receptors in hippocampal tissue [38] prompted the idea that glucocorticoid uptake by hippocampal cells may serve as a negative feedback to its putative inhibitory function over glucocorticoid secretion, but hormone implantation in the hippocampus has yielded contradictory results [67], It would be of interest to determine whether the growth suppressing and GH-inhibitory functions of hippocampal formation (present study and Borer et al [11] and of the rostral medial septal area [9] are mediated by somato statin.…”
Section: Discussionmentioning
confidence: 99%
“…provided that the nonstress environmental conditions were strictly controlled U hlir el al., 1974]. Hippocampal and amygaloid influences on the pituitary-adrenal axis are also disputed [review in K awakami et al, 1968;Moberg et al, 1971;Wilson and Critchlow, 1973;Matheson el al., 1971]. in our investigation, standard conditions were preserved throughout the experimental period and external disturbances were controlled.…”
Section: Discussionmentioning
confidence: 99%
“…Two weeks after bilateral transection of the fornix, no difference was found between morning and evening plasma corti costerone levels [Moberg et al, 1971]. However, it was observed that rostral septal lesions did not interfere with daily corticosterone fluctuations [Endroczi and N yakas, 1971] and that the hippocampal fornix system did not seem to be essential for the circadian rhythm in plasma corticosterone tilers [LengvAri and HalAsz, 1973;Wilson and Critchlow, 1973]. More recently, large lesions were either electrolytically or surgically [succion: Wilson and Critchlow, 1974] produced in the septal area and in the neigh boring nervous system structures (triangular nucleus, nucleus accumbens, fornix) of the rat.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the report of Moberg et al [1971], it appeared that the hippocampo-fornix system might be part of an essential neural sub strate for this endocrine rhythm. However, recent findings [Lengvari and H alAsz, 1973;W ilson and C ritchlow, 1973] suggest that this system is not essential for this function. Because the septum is another forebrain structure with appropriate connections to MBH [Raisman, 1966;M illhouse, 1969] and because it is capable of influencing the pituitary-adrenal axis [Usher et al, 1967;Seggif., 1968;Endroczi and N yakas, 1970; Seggie and Brown, 1971], the present experiments were designed to determine whether it is essen tial for rhythmic pituitary-adrenal function.…”
mentioning
confidence: 97%